Pro JPA 2 Mastering the Java™ Persistence API - Keith, Mike; Schincariol, Merrick; Keith, Jeremy (Apress : Imprint: Apress, 2010)
Pro JPA 2 introduces, explains, and demonstrates how to use the Java Persistence API (JPA). JPA provides Java developers with both the knowledge and insight needed to write Java applications that access relational databases through JPA. Authors Mike Keith and Merrick Schincariol take a hands-on approach to teaching by giving examples to illustrate each concept of the API and showing how it is used in practice. All of the examples use a common model from an overriding sample application, giving readers a context from which to start and helping them to understand the examples within an already familiar domain. After completing the book, you will have a full understanding and be able to successfully code applications using JPA. The book also serves as a reference guide during initial and later JPA application experiences. Hands-on examples for all the aspects of the JPA specification, based on the reference implementation of this specification A special section on migration to JPA Expert insight about various aspects of the API and when they are useful Portability hints to provide increased awareness of the potential for non-portable JPA code.